Il clima socio-politico prima delle elezioni europee 2019 - Maurizio Pessato; Rado Fonda; Riccardo Benetti (QOE-IJES, 2019)
The SWG Institute, together with other European partners (Sigmados, Insa, Opinion-Way and IBRiS), carried out some surveys in the months preceding the European Parliament election 2019 in several European countries in order to measure the political climate perceived by citizens on topics such as: European Union, institutions, emotions and main issues present in national political debates. In the analysis, the convergence and divergence features between Italian and European citizens will be highlighted. Furthermore, in addition to the data concerning the entire population, data regarding specific socio-demographic segments of the electorate will be compared.